English English - Setya Ayu Aprilia; Surjani Wonorahardjo; Yudhi Utomo (EKSAKTA: Journal of Sciences and Data Analysis, 2023)
An analytical method was carried out to identify volatile compounds that play a role in the coffee aroma and their stability. Because it is unstable at high temperatures, the effect of the injection temperature on the GC/MS column on changes in compounds profile was observed. The aim of this research is also to develop analytical methods for coffee analysis using TPI-GC/MS method. Samples of Lemar Arabica coffee were taken from the Wonosantri Abadi plantation, Singosari, Malang, and roasted at 210°C. The roasted coffee was extracted using the soxhletation method and methanol as solvent. The compound profiles were analyzed using the GC/MS method with injection temperatures of 40°C, 140°C, and 240°C. The results showed that ketones, esters, furans, and thiazoles play a role in the aroma of coffee. The compounds present in roasted coffee injected at 40°C were less than those at injection temperatures of 140°C and 240°C based on the chromatograms. The profile of the compound at the injection temperature of 240°C is also more diverse than the others because the large injection temperature allows decomposition to occur so that there are many fractional compounds from the thermal decomposition. Toluene is the most stable compound because it appears at all three injection temperatures. Non-volatile caffeine compounds were also detected at an injection temperature of 240°C.